Lethal severe congenital tracheal stenosis with tracheal ring complicating respiratory distress syndrome in an extremely premature infant: first reported case in Qatar with a literature review. Issue 12 (12th December 2020) - Nimeri, Nuha; Ali, Haytham; Mahmoud, Nazla
Abstract : In the context of prematurity, lethal congenital airways malforamtion can be masked by the symptoms of respiratory distress syndrome. A high index of suspicion is required. We present the case of a 28-week preterm infant, with atypical protracted respiratory insufficiency despite the escalation of mechanical ventilation. The possibility of airway obstruction was considered in view of severe chest retraction while on the mechanical ventilator. It was also difficult to pass suction catheters beyond a certain depth in the trachea; however, intubation of the upper trachea was accomplished twice without difficulty. Flexible bronchoscopy revealed complete tracheal ring with severe tracheal stenosis; there was no evidence of tracheo-oesophageal fistula. Due to advanced multi-organ dysfunction at diagnosis, a decision was made with the family to re-orientate from intensive care to compassionate care. Ethical considerations in similar cases should incorporate the improved outcomes of prematurity and recent advances in tracheal reconstruction.